Visuality and Identity in Post-millennial Indian Graphic Narratives - Varughese, E. Dawson. author. aut Link
XXVI, 119 p. 9 illus.
Keywords: “E. Dawson Varughese’s in-depth readings of the form and content of lesser known narratives that powerfully enrich the range and scope of alternative comics foreground the importance of a corpus that tackles all basic issues of post-millennial modernity in India.” —Jan Baetens, co-author with Hugo Frey of The Graphic Novel “The ‘old’ and the ‘new’ are brought together in interesting ways in her understanding of post-millennial Indian identities through the graphic novel and other visual cultural forms. Varughese offers us a compelling read and invaluable insights.” —Rajinder Dudrah, Birmingham City University, UK This book investigates the intersection of Indian society, the encoding of post-millennial modernity and ‘ways of seeing’ through the medium of Indian graphic narratives. If seeing in Indian cultures is a mode of knowing then what might we decode and know from the Indian graphic narratives examined here? The book posits that the ‘seeing’ of post-millennial Indian graphic narratives revolves around a visuality of the inauspicious, complemented by narratives of the same. Examining both form and content across nine Indian, post-millennial graphic narratives, this book will appeal to those working in South Asian visual studies, cultural studies and comics-graphic novel studies more broadly. E. Dawson Varughese is an independent, global cultural studies scholar, specialising in post-millennial Indian visual and literary cultures. She publishes on genre fiction, book cover design and public wall art. Her latest book is Genre Fiction of New India (Routledge, 2016). She was a Visiting Fellow at the University of Delhi in 2017. www.beyondthepostcolonial.com.